Whites and Browns: A Contrastive Study of Metadiscourse in English Newspaper Editorials - Shahid, Muhammad Imtiaz; Qasim, Hafiz Muhammad; Hasnain, Muhammad (Register Journal, 2021)
Metadiscourse is an interesting field of inquiry that is believed to play a vital role in organizing and producing persuasive writing. It is a set of linguistic devices used to communicate attitudes and mark the structural properties of a text. The study aimed to investigate whether native and non-native varieties of English varieties are similar or different from each other from the perspective of interactional meta-discourse markers. The study as contrastive rhetoric research scrutinized a corpus of 900 newspaper editorials (450 written in native English newspapers and 450 written in non-native English newspapers). Editorials were culled from 15 native English newspapers belonging to three native English countries, England, America, and New Zealand, and 15 non-native English newspapers belonging to three non-native English countries, Pakistan, India, and Sri Lanka. Based on the model of metadiscourse given by Hyland (2005), interactional metadiscourse resources were analyzed. The frequencies of interactional metadiscourse markers in both native and non-native varieties were counted and compared with each other. The results disclosed that there were worth-pointing differences between the native and non-native English editorialists in the use of interactional metadiscourse markers. Two different varieties of English editorials showed variations particularly in the use of hedging and self-mention markers. On the whole, findings suggested that the use of interactional metadiscourse markers in native English editorials were more frequent than those in non-native English editorials which made their writings more appealing and convincing context.Keywords: metadiscourse; native; non-native; newspaper; editorials